Model Pengelolaan Wisata Pantai Malalayang Kota Manado dengan Metode AHP - Pearl Lusye Wenas (HOSPITALITI DAN PARIWISATA, 2018)
Malalayang beach is one of the tourism and recreation place for the people of Manado and its surroundings. Although morphologically coastal tourism at Malalayang Beach classified as rocky beach, but this beach has always been a favorite for the people of Manado for recreation, especially on Sundays and holidays. The strategic location of this Malalayang beach is located near the highway and also located on the border between Manado city and Minahasa district. In its development, Malalayang beach for tourism has several problems in management. One of the problems faced is the frequent congestion caused by the lack of space for parking of visitors vehicles, In addition, inadequate facilities such as a place to rinse and toilet and the absence of a lifeguard that oversees the safety of visitors. From the various problems that arise required research for the selection of malalayang coastal tourism manado city with AHP method to know the right results. This research was conducted in Malalayang as coastal tourism area in Malalayang Dua Village, Malalayang District, Manado City. The length of this Malalayang tourist beach stretches approximately 1.25 km. using the quantitative method is elaborated using the AHP method. The study indicates that the Choice for Malalayang Coastal Tourism Manager is an alternative to the community with the highest priority value of 0,509. With a 0.08 inconsistency value that is below 0.1 then the results of this study may be accepted. Choice of Community as Malalayang Coast Tour manager get high priority value on Safety and Comfort criteria as well as criteria of Coastal Environment Quality. For tourist attraction criteria the highest value is private and for the criteria of facilities and infrastructure the highest value is the government. Suggestions that need to be considered is the need for collaboration both from the government and the private sector to manage the Malalayang Beach as tourist attraction. It also needs further research to find out the collaborative management model of Malalayang beach to be applied into tourism attraction management practices.